Effects of Stress Management Strategies to Public Elementary School Teachers’ Job Performance in San Felipe District, Schools Division of Zambales - Rico N. Falaminiano; Novrina Bigilda A. Orge (PT FORMOSA CENDEKIA GLOBAL, 2023)
Stress management is essential for good physical health, and it is especially important right now as the whole world addresses the coronavirus disease 2019 (COVID-19) pandemic (Galea, et. al., 2020). When individuals are more pessimistic, depressed, or anxious, their immune system goes down and produces more stress hormones, reducing their immunity and increasing inflammation (Casarella, 2019). This study determined the effects of stress management to one hundred thirty-four (134) public elementary school teachers’ job performance in San Felipe District, Schools Division of Zambales for School Year 2020-2021. There is significant difference on the dimensions towards dimension on effects of Stress Management Strategies. There is positively slight relationship between dimensions on the effects of Stress Management Strategies and Job Performance. It is recommended that Filipinos are noted and oriented to be “Family Centered” country. Continue practice the high value and love for the family; to maintain and continue to have a positive outlook in life and consider the problems as an awakening call and room for opportunity and improvement; that whenever feel severe stress, needs to consult medical experts.